Antimicrobial Resistance As A Global Health Threat: A Review Of Antibiotic Use Patterns, Policies, And Cross-Country Impacts - Ariska Agustina; Prima Paramita Putri; Kartika Destya Arini; Imas Nurhasanah; Evi Kusumastuti Setianingrum; Didin Sunardi; M. Amnurokhim Malahade (CV. Inara, 2025)
Antimicrobial resistance (AMR) is a global health challenge that threatens the effectiveness of infection treatment and the success of modern medical procedures. Inappropriate use of antibiotics, both in healthcare facilities and in the community, has accelerated the emergence of resistance. Irregular distribution, access without prescription, and the use of antibiotics for non-medical purposes such as agriculture have exacerbated the situation. Global policies, such as the Global Action Plan on AMR initiated by the WHO in 2015, aim to harmonize cross-border efforts to control AMR through a multisectoral One Health approach. However, its implementation still faces various challenges, particularly in low- and middle-income countries due to resource constraints, weak surveillance systems, and inadequate regulations. The cross-border impact of AMR is very real, including increased global health costs, the spread of resistant strains through human mobility, and inequalities in access to the latest generation of antibiotics. Therefore, global synergy is needed to improve antibiotic governance, strengthen surveillance systems, and educate the public and health workers. This article reviews the latest literature and policies on AMR to understand the dynamics of antibiotic use, global policy challenges, and the direction of cross-border solutions.